Jeff Wall: The Connection Between Photography and Cinematography (Asian Journal of Social Science Studies, 2022)
This paper will focus on the dialogue between photography and cinema by evaluating film theories used in Jeff Wall‟s photos. In order to break the restrictions between different media and art forms, Wall expanded the space of photography and breaks the shackles of conventional art, thereby gaining greater freedom of expression.